PEMBERIAN BIOCHAR DIPERKAYA TRICHODERMA DENGAN PENAMBAHAN AMONIUM NITRAT UNTUK MENINGKATKAN PERTUMBUHAN BIBIT KOPI ARABIKA - Wuri Nastiti; Cahyo Prayogo (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2020)
Coffee is a source of foreign exchange that plays an important role in the development of the plantation industry. However, many coffee-producing regions have experienced quite detrimental yields in recent years due to the rust of coffee leaves (Hemileia vastatrix), a parasitic fungus that reduces yields and that can ultimately kill coffee plants. The use of biochar enriched with Trichoderma can help to improve soil conditions and increase crop production because biochar can increase the availability of N and P. Trichoderma as a biocontrol agent that can help in solving the problem of coffee leaf rust. This study that was conducted at Gondorejo Village, Oro-oro Ombo sub-district, Batu District used a completely randomized design with seven treatments and four replications. The results showed that the application of media with a composition of 1% biochar enriched with Trichoderma supported the growth of Arabica coffee seedlings at the age of 3 months. It can be seen from the available N content, which showed an increase and the number of leaves which had the highest increase among other treatments. This indicated that the composition was sufficient to support good media for the growth of Arabica coffee seedlings.